A Novel Insecticidal Spider Peptide that Affects the Mammalian Voltage-Gated Ion Channel hKv1.5 - Alvarado, Diana; Cardoso-Arenas, Samuel; Corrales-García, Ligia-Luz; Clement, Herlinda; Arenas, Iván; Montero-Dominguez, Pavel Andrei; Olamendi-Portugal, Timoteo; Zamudio, Fernando; Csoti, Agota; Borrego, Jesús; Panyi, Gyorgy; Papp, Ferenc; et al. (Frontiers in Pharmacology, 2021)
Spider venoms include various peptide toxins that modify the ion currents, mainly of excitable insect cells. Consequently, scientific research on spider venoms has revealed a broad range of peptide toxins with different pharmacological properties, even for mammal species. In this work, thirty animal venoms were screened against hKv1.5, a potential target for atrial fibrillation therapy. The whole venom of the spider O. supermirabilis, which is also insecticidal to house crickets, caused voltage-gated potassium ion channel modulation in hKv1.5. Therefore, a peptide from the spider O. supermirabilis venom, named Osu1, was identified through HPLC reverse-phase fractionation. Osu1 displayed similar biological properties as the whole venom; so, the primary sequence of Osu1 was elucidated by both of N-terminal degradation and endoproteolytic cleavage. Based on its primary structure, a gene that codifies for Osu1 was constructed de novo from protein to DNA by reverse translation. A recombinant Osu1 (rOsu1) was expressed using a pQE30 vector inside the E. coli SHuffle expression system. rOsu1 had voltage-gated potassium ion channel modulation of human hKv1.5, and it was also insecticidal as the native toxin. Due to its novel primary structure, and hypothesized disulfide pairing motif, Osu1 may represent a new family of spider toxins.